Impacts of dioxin exposure on brain connectivity estimated by DTI analysis of MRI images in men residing in contaminated areas of Vietnam - Thao, Pham Ngoc; Nishijo, Muneko; Tai, Pham The; Nghi, Tran Ngoc; Yokawa, Takashi; Hoa, Vu Thi; Tien, Tran Viet; Kien, Nguyen Xuan; Anh, Tran Hai; Nishino, Yoshikazu; Nishijo, Hisao (Frontiers in Neuroscience, 2024)
This study was undertaken to investigate the impact of dioxin exposure on white matter microstructure in men living in the most severely dioxin-contaminated areas in Vietnam. In 2019 brain MRI scans from 28 men living near Bien Hoa airbase were obtained at Dong Nai General Hospital, Vietnam, on a 3T scanner using a conventional diffusion tensor imaging sequence. Two exposure markers were indicated by perinatal exposure estimated by assessment of maternal residency in a dioxin-contaminated area during pregnancy and by measurement of blood dioxin levels. A general linear model was used to compare fractional anisotropy (FA) values in 11 white matter tracts in both hemispheres between groups with and without perinatal dioxin exposure and groups with high and low blood dioxin levels after adjusting for covariates.The adjusted mean FA value in the left cingulum hippocampal part (CGH) was significantly lower in the perinatal dioxin exposure group compared with the group without perinatal dioxin exposure. The high blood TCDD group showed significantly reduced FA values in the left and right CGH and right uncinate fasciculus (UNC). Moreover, the high blood TEQ-PCDDs group showed significantly lower FA values in the left and right CGH and the left UNC. There were no significant differences in FA values between the groups with high and low TEQ-PCDFs levels or between the groups with high and low TEQ-PCDD/Fs levels. It was concluded that dioxin exposure during the perinatal period and adulthood may alter the microstructure of white matter tracts in individuals with neurodevelopmental disorders.